The cotton charcoal rot causal agent, Macrophomina phaseolina, biological and chemical control - Degani, Ofir; Gordani, Asaf; Dimant, Elhanan; Chen, Assaf; Rabinovitz, Onn (Frontiers in Plant Science, 2023)
The fungus Macrophomina phaseolina causes charcoal rot disease (CRD) in cotton, whose symptoms develop in the late stages of growth and result in wilting and death. Despite significant research efforts to reduce disease incidences, effective control strategies against M. phaseolina are an ongoing scientific effort. Today's CRD control tends toward green options to reduce the chemicals' environmental footprint and health risks. Here different Trichoderma species were examined separately and in combination with Azoxystrobin (AS, at low dose) in semi-field open-enclosure pots and a commercial field throughout a full season. In the pot experiment, the T. asperellum (P1) excelled and led to improvement in growth (13-14%, day 69) and crops (the number of capsules by 36% and their weight by 78%, day 173). The chemical treatment alone had no significant impact. Adding AS improved the effect of T. longibrachiatum (T7507) and impaired P1 efficiency. Real-time PCR Monitoring of the pathogen DNA in the plants' roots at the harvest (day 176) revealed the efficiency of the combined treatments: T. longibrachiatum (T7407, T7507) + AS. In a commercial field, seed dressing with a mixture of Trichoderma species (Mix of P1, T7407, Trichoderma sp. O.Y. 7107 isolate) and irrigation of their secreted metabolites during seeding resulted in the highest yields compared to the control. Applying only AS irrigation at a high dose (4,000 cc/ha), with the seeding, was the second best in promoting crops. The molecular M. phaseolina detection showed that the AS high dose and the biological Mix treatments were the most effective. Reducing the AS chemical treatment dosages by half impaired its effectiveness. Irrigation timing, also studied here, proved vital. Early water opening during the late spring suppresses the disease outburst and damage. The results demonstrated the benefits of CRD bio-shielding and encouraged to explore the potential of a combined bio-chemo pest control approach. Such interphase can be environmentally friendly (reducing chemical substances), stabilize the biological treatment in changing environmental conditions, achieve high efficiency adapted to severe CRD cases, and reduce the development of fungicide resistance.